Applications in Stimulated Emission Depletion Microscopy: Localization of a Protein Toxin in the Endoplasmic Reticulum Following Retrograde Transport. (2nd November 2016) - Herrera, Cristina; Mantis, Nicholas J.; Cole, Richard
Abstract: Retrograde transport is a process in which proteins are trafficked from the plasma membrane and endosomes to biosynthetic and secretory organelles, namely the Golgi apparatus and endoplasmic reticulum (ER). A number of plant and bacterial toxins, including cholera toxin and ricin toxin, exploit retrograde transport to gain entry into host cells, although the specifics of this process have remained difficult to probe by laser scanning confocal microscopy (LSCM). Here we demonstrate the use of super-resolution and live-cell imaging [stimulated emission depletion (STED)] to visualize exogenously applied ricin toxin within the ER. The improved resolution obtained by STED, as compared with LSCM (0.09 versus 0.19 μ m), provides a more accurate determination of the amount of ricin that had trafficked to the ER.